Atributos químicos do solo de várzea tropical cultivado com arroz irrigado em razão do manejo do nitrogênio - Gonçalves, Gustavo de Melo Oliveira (2016)
In the last years, due to the government effort, especially in the Tocantins State, there have been significante increase on flooded rice production areas. However, there are few studies about nitrogen sources and doses in that region, which could improve the nitrogen efficiency use and provide higher incomes for farmers. This study aimed to determine the effects of different sources and doses of nitrogen in flooded lowland soils in the pH, redox potential and the concentration of ions in the soil solution in order to obtain the economicallyand environmentally best mineral nitrogen source and dose. The samples were collected in the 2014/2015 season at the Embrapa Rice and Beans Experimental Field - Palmital Farm-, in a Dystric Gleysol. The design was a complete randomized blocks, with four replications, two sources of nitrogen (common urea and slow release urea), three nitrogen rates (30, 70, 150 kg ha-1), and a control, without any N application.Soil solution samples were collected weekly, during the flooded period in rice cultivation, BRS Catiana genotype. The pH analysis and Eh (redoxpotential) were immediately read, just after the soil solution sampling, in the field, and thenHCl (2M) acidified,, and immediately frozen for later analysis of the following ions: Ca, Mg, K, Fe, Zn, Mn, MOS, NO3- and NH4+. The sources used did not affect the release of nutrients dynamics to the soil solution. The anaerobic condition caused changes in the Eh and ions solubility in the soil solution. The doses applied changed Ca and MOS concentrations in solution, and the dose of 150 kg ha-1 N showed the highest values for both.